Role of NGOs in agricultural research in India A passage for transfer of technology from lab-to-land - Hegde, Narayan G. (Indian Farming, 2018)
There are very few NGOs who are engaged in agricultural research, although research backup can strengthen the development programme. However, some of these NGOs have made outstanding contribution to agricultural development through research and technology transfer. As NGOs have good knowledge about local agricultural situation and close association with farmers, they are in a better position to identify the challenges in agriculture. Hence, the research institutions and Krishi Vigyan Kendras can associate with NGOs having good track record to carry out field research trials and technology transfer. Such associations will empower the NGOs and help farmers to enhance their agricultural production.